Typical Language Mistakes and the Ways of Organizing their Correction in the Course of Teaching the Ukrainian language (for Special Purposes). - Старова, Е. А. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The article is devoted to the typical modern literary Ukrainian language rules breakings, which are common in the speech of students and cadets. Techniques of the correction of errors, that can be easily and efficiently implemented in teaching the course “Ukrainian language (for special purposes)”, have been systematized